Causes and countermeasures for the increased infection and COVID-19 mortality rates in patients with schizophrenia - Zhen-Ying Li; Yu-Qian Li; Jing-Ru Zhou; Jie Wang; Kun-Ze Liu; Peng Wang; Chun-Mei Gong; Han Wang; Yu-Jing Zhang; Yu Cao; Yue Gu; Han-Bo Zhang; et al. (IBRO Neuroscience Reports)
Schizophrenia (SCZ) is a common psychiatric disorder that has a complex pathological mechanism. During the Coronavirus disease 2019 (COVID-19) epidemic, patients with SCZ had substantially higher rates of infection with SARS-CoV-2, the virus that causes COVID-19, as well as higher COVID-19 mortality relative to patients with other mental disorders. However, the reasons for these increased rates in patients with SCZ remain unknown. In this review, we hypothesize that certain molecular pathways exhibit abnormal function in both COVID-19 and SCZ, with a focus on those related to energy metabolism dysregulation, immune system disruption, and abnormalities of the central nervous system. We review that dysregulation of energy metabolism can result in disruptions to the immune system and abnormalities within the central nervous system (CNS). Furthermore, immune system disturbances may also contribute to CNS abnormalities in both SCZ and COVID-19. We also discuss macro-factors associated with the high infection and mortality rates of COVID-19 in patients with SCZ, including sociodemographic factors, reduced access to psychiatric healthcare, structural barriers to COVID-19 vaccination, and proposed approaches to mitigate these macro-factors.